CHAT GPT technology use in scientific research between advantages and Risks (Revue El-Wahat pour les Recherches et les Etudes, 2026)
Artificial intelligence tools are robots capable of doing tasks with efficiency ,and it helps in increasing productivity in the field of scientific research ,the best tools of artificial intelligence is CHAT GPT,many studies have been done about using this technique and these studies approved that CHAT GPT has the ability to enter new horizons in scientific research ,especially in fields of creating new ideas and promote scientific standards beside that ,these studies showed some fears and had considered this technique controversial due to the risks that could result from it especially in the field of higher education and scientific research .therefore in this study we will try to  spot light on some advantages that this technique holds in scientific research and point out the risks that it may occurs  after using it in this field .